Refrigeration of an array of cylindrical nanosystems by superfluid helium counterflow. (January 2017) - Sciacca, M.; Sellitto, A.; Galantucci, L.; Jou, D.
Highlights: Cooling of an array of heat-producing nanosystems by superfluid-helium counterflow. Thermal conductivity through arrays of orthogonal cylinders in counterflow channel. The maximum cooling capacity in the laminar regime and below the lambda temperature. Abstract: Motivated by the challenge of computer refrigeration, we study the limits set by the transition to quantum turbulence on the cooling of an array of heat-producing cylindrical nanosystems by means of superfluid-helium counterflow. The effective thermal conductivity in laminar counterflow superfluid helium is obtained in channels with rectangular cross section, through arrays of mutually parallel cylinders and in the combined situation of arrays of orthogonal cylinders inside the rectangular channel. The maximum cooling capacity is analyzed on the condition that turbulence is avoided and that the highest temperature does not exceed the lambda temperature.